Cryptosporidium avium n. sp. (Apicomplexa: Cryptosporidiidae) in birds - Holubová, Nikola; Sak, Bohumil; Horčičková, Michaela; Hlásková, Lenka; Květoňová, Dana; Menchaca, Sarah; McEvoy, John; Kváč, Martin (Parasitology research, 2016)
The morphological, biological, and molecular characteristics of Cryptosporidium avian genotype V are described, and the species name Cryptosporidium avium is proposed to reflect its specificity for birds under natural and experimental conditions. Oocysts of C. avium measured 5.30-6.90 μm (mean = 6.26 μm) × 4.30-5.50 μm (mean = 4.86 μm) with a length to width ratio of 1.29 (1.14-1.47). Oocysts of C. avium obtained from four naturally infected red-crowned parakeets (Cyanoramphus novaezealandiae) were infectious for 6-month-old budgerigars (Melopsittacus undulatus) and hens (Gallus gallus f. domestica). The prepatent periods in both susceptible bird species was 11 days postinfection (DPI). The infection intensity of C. avium in budgerigars and hens was low, with a maximum intensity of 5000 oocysts per gram of feces. Oocysts of C. avium were microscopically detected at only 12-16 DPI in hens and 12 DPI in budgerigars, while PCR analyses revealed the presence of specific DNA in fecal samples from 11 to 30 DPI (the conclusion of the experiment). Cryptosporidium avium was not infectious for 8-week-old SCID and BALB/c mice (Mus musculus). Naturally or experimentally infected birds showed no clinical signs of cryptosporidiosis, and no pathology was detected. Developmental stages of C. avium were detected in the ileum and cecum using scanning electron microscopy. Phylogenetic analyses based on small subunit rRNA, actin, and heat shock protein 70 gene sequences revealed that C. avium is genetically distinct from previously described Cryptosporidium species.
Keywords: kur domácí; Animals; Morphology; Ileum; Female; feces; Feces; Melopsittacus; myši SCID; Chickens; ileum; Cryptosporidium avium; Cryptosporidium avian genotype V; ženské pohlaví; Poultry Diseases; oocysty; Cryptosporidiosis; Oocysts; Mice; nemoci drůbeže; Cecum; Mice, Inbred BALB C; Mice, SCID; myši; Phylogeny; Molecular analyses; Transmission studies; myši inbrední BALB C; kryptosporidióza; zvířata; fylogeneze; cékum; Cryptosporidium